Nanoparticle-Based Systems for Delivery of Protein Therapeutics to the Spinal Cord - Infante, Juan C. (Frontiers in Neuroscience, 2018)
Recent studies have demonstrated that delivery of protein therapeutics to the spinal cord may promote functional axon regeneration, providing a pathway for recovery of certain motor skills. The timeframe for delivery of protein therapeutics, however, must be modulated to prevent bulk release of the therapeutics and minimize the frequency of implantations. This perspective examines both affinity-based and nanoparticle-based strategies for delivery of neurotrophic factors (NFs) to the spinal cord in an effective, safe, and tunable manner.